The Impact of Environmental, Social and Governance, Sustainable Financial Performance, Ownership Structure, and Composition of Company Directors on Tax Avoidance: Evidence from Indonesia - Hidayat, Kadarisman; Zuhroh, Diana (International Journal of Energy Economics and Policy, 2023)
The aim of the present study is to empirically estimate the impact of ESG, composition of company directors, ownership structure and financial performance on tax avoidance. To achieve the study objectives, 114 companies listed on Indonesian Stock Exchange market are selected covering the data span over 2013-2020 period. Institutional ownership, female directors, ESG performance, return on assets and firm size are taken as the measures of ownership structure, composition of company directors, ESG and financial performance respectively. Empirical analysis is carried out using Fixed Effects Model as it is found as the appropriate estimation technique in Hausman test and Breusch-Pagan test. According to the study findings, EGS, ownership structure, composition of company directors all have significant and negative impact on tax avoidance. Among financial performance indicators, only firm size has negative and significant impact while return on assets has no significant effect on tax avoidance. The study recommends the firms or businesses to pay attention to ESG factors, institutional ownership and female directorship as these factors are found to have prominent role in improving tax avoidance behavior.